FREQUENCY OF CHRONIC PERIODONTITIS IN A CROSS SECTION OF PAK ARMY PERSONNEL: Chronic Periodontitis - Babar, Zubair; Chaudhry, M. Parwez; Akhtar, Fahmeed (Pakistan Armed Forces Medical Journal, 2008)
Objective: To determine the frequency of periodontitis in lower ranks of Pakistan Army. Designed: A descriptive study.. Place and Duration of Study: The study was conducted at Armed Forces Institute of Dentistry, Rawalpindi between Aug 2003 and Feb 2005. Subjects and Methods: This is a in which Periodontal status of maxillary and mandibular incisors and permanent first molars in five hundred and fifteen personnel of the Pakistan Army was evaluated using plaque index, probing depths, attachment loss, bleeding upon probing, tooth mobility and presence of calculus. Results: One hundred and sixty five (32.04%) subjects had 5 mm or deeper probing depths as well as associated attachment loss of at least 2 mm and were considered to be suffering from Chronic Periodontitis. Conclusion: The study detected that a noticeable percentage of subjects in this population had a substandard level of oral hygiene and consequently suffered from Chronic Periodontitis.